BRAC-donor consortium RDP II : BRAC Bank review - Houghton, Mary; Grzywinski, Ronald (© BRAC, 2016)
Memorandum: To: Members of BRAC Governing body and BRAC donor's. From: Mary Houghton and Ronald Grzywinski, October, 1992 BRAC Bank Review.